Chlamydial clinical isolates show subtle differences in persistence phenotypes and growth in vitro. Issue 3 (19th March 2021) - Thomas, Mark; Lawrence, Amba; Kroon, Samuel; Vodstrcil, Lenka A.; Phillips, Samuel; Hocking, Jane S.; Timms, Peter; Huston, Wilhelmina M.
Abstract : Urogenital Chlamydia trachomatis infection is the most common sexually transmitted bacterial infection throughout the world. While progress has been made to better understand how type strains develop and respond to environmental stress in vitro, very few studies have examined how clinical isolates behave under similar conditions. Here, we examined the development and persistence phenotypes of several clinical isolates, to determine how similar they are to each other, and the type strain C. trachomatis D/UW-3/Cx. The type strain was shown to produce infectious progeny at a higher magnitude than each of the clinical isolates, in each of the six tested cell lines. All chlamydial strains produced the highest number of infectious progeny at 44 h post-infection in the McCoy B murine fibroblast cell line, yet showed higher levels of infectivity in the MCF-7 human epithelial cell line. The clinical isolates were shown to be more susceptible than the type strain to the effects of penicillin and iron deprivation persistence models in the MCF-7 cell line. While subtle differences between clinical isolates were observed throughout the experiments conducted, no significant differences were identified. This study reinforces the importance of examining clinical isolates when trying to relate in vitro data to clinical outcomes, as well as the importance of considering the adaptations many type strains have to being cultured in vitro .